Instructional Improvement and the Control of Schools - Murphy, Joseph ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This paper reviews, in two parts, discoveries about control in 12 instructionally effective school districts (IESD) in California. In part one, after describing six ways to view administrative control, this report provides a brief description of the study, presents findings on the use of selected control mechanisms, and reviews what was learned about the the dynamics of control and empowerment in these districts. Part two consists of a discussion concerning the methodological problems in studies of control in educational organizations. The conclusion notes a need to view control and empowerment as interrelated, not opposite constructs. (JAM)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 5-9, 1988).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Organization; Educational Assessment; Educational Quality; Elementary Secondary Education; Instructional Improvement; Organizational Effectiveness; Power Structure; School Effectiveness; School Role; School Supervision; California; Speeches/Meeting Papers; Reports, Research